Advanced polymer nanoparticles : synthesis and surface modifications - Mittal, Vikas (CRC Press, 2011)
Polymer nanoparticles are an important class of polymeric materials that are required for a number of commercial applications. This book presents the developments in the synthesis and surface modification techniques to generate advanced polymer nanoparticles. It discusses emulsion polymerization, and miniemulsion polymerization.
Keywords: Polymerization.; Nanoparticles.; Polymers -- Surfaces.; elektronické knihy; electronic books